PENANAMAN NILAI KARAKTER RELIGIUS DENGAN PEMBIASAAN - Nuarta Rosa Sasmita; Hafidz Hafidz (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
Religious character has an important role as a foundation for life that is not only done at school through learning activities but also by habituation in life. The purpose of this study is to find out the habituation activities at school and the improvement of religious character carried out by religious habituation as well as the supporting and inhibiting factors in the implementation of habituation. This study applied a descriptive qualitative research approach, with the principal and Islamic Religious Education (PAI) teachers as the research subjects. The results showed that there are several religious habits at SMP Muhammadiyah 5 Surakarta in improving the religious character of students, such as shoalt dhuha in the congregation, murojaah ba'da dhuha, the application of the 5S principle, which includes smiles, greetings, greetings, politeness, and courtesy, along with the cultivation of habits to perform prayers. dzuhur and ashar in the congregation and habituation of Friday recitation every month. From this habituation, there is an increase in the religious character of students in several ways, such as discipline, a love of reading and memorizing the Qur'an, and a sense of responsibility. Supportive factors include support from parents and the availability of adequate school facilities. Conversely, the hindering factors involve differences in students' backgrounds and the influence of the environment as well as interactions between learners.